Understanding the diagnostic yield of current endoscopic biopsy for gastric neoplasm: A prospective single-center analysis based on tumor characteristics stratified by biopsy number and site. Issue 30 (July 2016) - Kwack, Won G.; Ho, Won J.; Kim, Jae H.; Lee, Jin H.; Kim, Eo J.; Kang, Hyoun W.; Lee, Jun K.
Abstract : Abstract: Although there are general guidelines on endoscopic biopsy for diagnosing gastric neoplasms, they are predominantly based on outdated literature obtained with fiberscopes without analyses specific to tumor characteristics. This study aims to comprehensively characterize the contemporary endoscopic biopsy by determining the diagnostic yield across different lesion morphologies and histological stages, especially exploring how the number and site of biopsy may influence the overall yield. Biopsy samples from suspected gastric neoplasms were collected prospectively from May 2011 to August 2014 in a tertiary care medical center. A standardized methodology was used to obtain a total of 6 specimens from 2 defined sites per lesion. Rate of positive diagnosis based on the biopsy number and site was assessed for specific gastric lesion morphologies and histological stages. A total of 1080 biopsies from 180 pathologically diagnosed neoplastic lesions in 176 patients were obtained during the study. For depressed/ulcerative and polypoid lesions, the yield was already >99% by the fourth biopsy without further gain from additional biopsies. Lower overall yield was observed for infiltrative lesions (57.1% from 4 biopsies). The site of biopsy did not influence the diagnostic yield except for with infiltrative lesions in which biopsies from thickened mucosal folds were of higher yield than erosive regions. Obtaining 4 specimens may be sufficient for accurate diagnosis of a depressed/ulcerative or polypoid gastric lesion regardless of its histological stage. For infiltrative lesions, at least 5 to 6 biopsies per lesion with more representative sampling from thickened mucosal folds may be preferable. Abstract : Supplemental Digital Content is available in the text